Ethnobotany of medicinal plants in the quilombola community Arruda Sítio, Araripe-CE: knowledge, health and sustainability (Revista Brasileira de Plantas Medicinais, 2020)
The objective of this study was to conduct an ethnobotanical study in the Sítio Arrudas quilombola community, in the municipality of Araripe-CE, on the use of medicinal plants in the territory, their perceptions, social, cultural and economic importance. The methodology used was based on the qualitative research, of the descriptive analytical type through semi-stuttered interview and in loco observation. Various medicinal plants used are grown in their backyards; other plants are mined in the native forest surrounding the community. There are also medicinal plants, large trees preserved close to the dwellings, such as: Eucalyptus globulus, Myrrondruon urundeuva, Cedrela fissilis, Ziziphus joazeiro and Linus usitatissimum. Uses and customs have an influence on respect for ancestry, on the value of the perpetuation of the onlendings learned, and on the trust that the community uses when using medicinal plants for therapeutic treatments.